The mediating role of professional identity in the relationship between gender misconceptions and occupational stigma among male nursing students - Shaimaa Mohamed Amin; Doaa El Demerdash; Ahmed Abdellah Othman; Mohamed Ali Zoromba; Heba Emad El-Gazar; Mohamed Hussein Ramadan Atta; Ali Albzia; Mahitab Mohamed Abdelrahman; Ibrahim Alasqah; Haitham Mokhtar Mohamed Abdallah (BMC Nursing)
Abstract Background Male nursing students often face unique challenges related to their professional identity, stigma associated with the nursing profession, and gender-related misconceptions. These factors can influence their academic and career development. Understanding these elements is crucial for improving the support systems and educational environments for male nursing students. Aim This study aimed to assess the professional identity, occupational stigma, and gender misconceptions among male nursing students at Sohag University, Egypt, and explore the relationships between these factors. Methods A cross-sectional descriptive design was used. A total of 308 male nursing students enrolled in the 2024–2025 academic year were selected through systematic random sampling. Data were collected using three validated instruments: the Professional Identity Scale for Male Nursing Students, the Nurse Occupational Stigma Scale, and The gender misconceptions of men in nursing scale. Descriptive statistics, Pearson’s correlation, and Linear regression analysis were employed to analyze the data. JASP 0.14.1.0 was used for testing the mediating role of male identity between der misconceptions and nurse occupational stigma through SEM Module through SEM Module with Delta method standard errors. Results The participants’ mean score for professional identity was 38.5 (SD = 6.4). The mean score for the Nurse Occupational Stigma Scale was 53.2 (SD = 8.1), The GEMINI scale showed a mean score of 55.3 (SD = 7.9). In addition, revealed a significant positive correlation between professional identity and stigma (r = .52, p < .001), and a negative correlation between professional identity and gender misconceptions (r = -.45, p < .001). Also, stigma and gender misconceptions significantly predicted professional identity (R² = 0.38, p < .001). Conclusion The study highlights significant associations between male nursing students’ professional identity, occupational stigma, and gender misconceptions. Addressing stigma and misconceptions can enhance the development of professional identity among male nursing students, fostering a more supportive academic environment. Clinical trial number Not applicable.